2012
DOI: 10.1097/sle.0b013e318247d966
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Ligasure Versus Stapled Hemorrhoidectomy

Abstract: Stapled hemorrhoidectomy (SH) and Ligasure hemorrhoidectomy (LH) are standard for hemorrhoidal disease treatment, but the surgical principle is different. This randomized clinical trial compared the 2 methods. We included 98 patients with grade 3 hemorrhoidal disease: 46 patients treated by SH and 52 patients by LH. Incidence of complications, recurrence, postoperative pain, wound healing time, and time off everyday activity were observed. The follow-up period was 24 months. We found that LH has a significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…In SH group in our study post-operative pain was observed in slightly more number of patients, probably due to anal spasm, comparable results were observed by Basdanis G et al 1,4,7,8 Despite positioning the stapled line above dentate line and absence of external wound, pain was observed. In due course of time prolapsed haemorrhoids shrinked.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In SH group in our study post-operative pain was observed in slightly more number of patients, probably due to anal spasm, comparable results were observed by Basdanis G et al 1,4,7,8 Despite positioning the stapled line above dentate line and absence of external wound, pain was observed. In due course of time prolapsed haemorrhoids shrinked.…”
Section: Discussionsupporting
confidence: 77%
“…1,3,4,6,[8][9][10][11][12][13][14][15][16][17][18] Anal/rectal stenosis observed was about five times higher in EH group in spite of leaving islands of normal skin and mucosa to avoid stricture formation, which was managed conservatively. Recurrence, residual skin tags and prolapse were observed to be three times higher in SH group, comparable results were observed by Yang J et al [1][2][3][4][5] …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Patients characteristics extracted from these trials are presented in Table 1. [3][4][5][6][7] Patients characteristics extracted from these trials are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1 About 5% of the general population has some degree of haemorrhoidal disease especially those elder than 40 years. 2 Haemorrhoids can be external or internal relative to dentate line. 3 Internal haemorrhoids are divided in to four grades by Goligher system.…”
Section: Introductionmentioning
confidence: 99%